Combining High Oleic Acid Trait and Resistance to Late Leaf Spot and Rust Diseases in Groundnut (Arachis hypogaea L.) - Deshmukh, Dnyaneshwar B.; Marathi, Balram; Sudini, Hari Kishan; Variath, Murali T.; Chaudhari, Sunil; Manohar, Surendra S.; Rani, Ch V. Durga; Pandey, Manish K.; Pasupuleti, Janila (Frontiers in Genetics, 2020)
High oleic trait, resistance to rust and late leaf spot (LLS) are important breeding objectives in groundnut. Rust and LLS cause significant economic loss, and high oleic trait is an industry preferred trait that enhances economic returns. This study reports marker-assisted selection to introgress high oleic content, resistance to LLS and rust into Kadiri 6 (K 6), a popular cultivar. The alleles for target traits were selected using linked allele-specific, simple sequence repeats (SSRs) and single nucleotide polymorphic (SNP) markers. The F1s (384), intercrossed F1s (441), BC1F1s (380), BC1F2s (195) and BC¬1F3s (343) were genotyped to obtain desired allelic combination. Sixteen plants were identified with homozygous high oleic, LLS and rust resistance alleles in BC1F2, which were advanced to BC1F3 and evaluated for disease resistance, yield governing and nutritional quality traits. Phenotyping with Near-Infrared Reflectance Spectroscopy (NIRS) identified three lines (BC1F3-76, BC1F3-278 and BC1F3-296) with >80% oleic acid. The identified lines exhibit high levels of resistance to LLS and rust diseases (score of 3.0-4.0) with preferred pod and kernel features. The selected lines are under yield testing trials in multi-locations for release and commercialization. The lines reported here demonstrated combining high oleic trait with resistance to LLS and rust diseases.